Design of a Website-Based Personnel Information System at PT Indiga Nusa Digitama (Inditama) - Mustikasari Putri, Dewi; Apandi, Tri Herdiawan; Khoirunnisa, Nurfitria; Saputra, Yogi (Departement Information Systems Universitas Kebangsaan Republik Indonesia, 2024)
This research focuses on the development of a personnel information system for PT. Indiga Nusa Digitama (Inditama), aimed at streamlining the management of attendance data, leave applications, and official travel documents (Surat Perjalanan Dinas or SPD). The primary objective is to enhance operational efficiency, minimize errors, and accelerate administrative processes, which were previously manual and prone to inefficiencies. A systematic approach using the waterfall methodology was employed, beginning with a thorough needs analysis conducted through observations, interviews, and literature reviews to identify existing challenges and requirements. The system design leveraged Unified Modeling Language (UML) for structural modeling and Figma for user interface design, ensuring a user-friendly and visually coherent experience. The resulting system effectively automated key processes, centralizing attendance, leave, and SPD data into a unified platform. This improved data organization, accessibility, and archival reliability, while fostering compliance with company policies and enhancing overall administrative transparency. The study also identifies potential future enhancements, including the integration of mobile-based features, payroll management, and recruitment modules, to broaden the scope of the system. These additions are expected to further optimize human resource management, deliver a more comprehensive solution for personnel administration, and contribute positively to the company’s strategic growth. Through this research, PT. Inditama gains a scalable and efficient system capable of supporting its evolving operational needs.